Monitoring evolution of debris-filled damage using pre-modulated wave and guided wave ultrasonic testing (GWUT) - Samuel, Olisa C.; Starr, Andrew; Muhammad, Khan A. (Elsevier, 2022)
Metals are essentially used to construct structures of high economic importance, but their service life is shortened by damage such as crack, corrosion, cavity, and dents. Damage to structure causes gradual degradation of its strength and compromises its load-carrying capacity. Some damage could be designed against but pitting corrosion, especially when it is filled with debris that would hide it and deepen its perforation activities. In this work, monitoring the evolution of debris-filled damage in structure is studied using pre-modulated wave and guided wave ultrasonic testing (GWUT). The structural responses in the varying percentage of debris-filled damage were processed using Fast Fourier Transform (FFT), Hilbert Transform (HT) and correlation techniques. The regression analysis of debris-filled damage resulted in empirical predictive models that could detect the damage and percentage of debris that might have filled it with average percentage errors of 1.34 and 0.21, respectively. The debris in the damage caused an overmodulation of the high-frequency signal. The intensity of the lower sideband (LSB) was observed to be very sensitive to variations in the damage than the upper sideband (USB). The transmission power efficiency of modulation sidebands increased proportionally with debris-filled damage percentage and could serve as a damage index.
Keywords: ultrasonics; guided wave; corrosion; modulation; damage